1985
DOI: 10.1111/j.1469-8749.1985.tb03800.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Neuromotor Behavior of Preterm and Fullterm Infants in the First Year of Life: A Preliminary Report

Abstract: SUMMARY A follow‐up study of 150 fullterm and preterm infants was conducted to determine the similarities and differences in neuromotor behavior during the first year of life. Three groups (healthy fullterm, healthy preterm, sick preterm) were compared at three, six, nine and 12 months of age. In general, fullterm infants were more similar in their responses to the Neuromotor Behavioral Inventory and more consistently advanced than some preterm infants at all four examinations. The greatest distinction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
0
12

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 23 publications
(9 reference statements)
3
7
0
12
Order By: Relevance
“…Our observation concerning the association of preterm birth with late walking attainment was consistent with the data of previous studies [19,21,28]. In this study, the age of onset of the preterm infants (mean 12.8 months) was about one month later than that of the normal term infants (mean 11.9 months) after correction for prematurity.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our observation concerning the association of preterm birth with late walking attainment was consistent with the data of previous studies [19,21,28]. In this study, the age of onset of the preterm infants (mean 12.8 months) was about one month later than that of the normal term infants (mean 11.9 months) after correction for prematurity.…”
Section: Discussionsupporting
confidence: 94%
“…Some found that preterm infants attain walking ability at older ages than their normal term counterparts when corrected for prematurity [19][20][21]; while others reported similar ages [22,23]. Only two studies have assessed the qualitative aspects of early walking movement in preterm infants.…”
Section: Introductionmentioning
confidence: 98%
“…Preterm infants often have low PMT, but seem to develop exaggerated AMP. This behaviour is most obvious in the trunk and legs and has often been described as hyperextension in preterm infants after term age [9][10][11][12][13][14][15] . It has been argued that usually this is a transient phenomenon and, unless related to other neurological signs, is disregarded as being of no importance for further development 16,17 .…”
mentioning
confidence: 99%
“…These mothers then feel unable to properly care for their children, which in turn heightens their anxiety ͑Barnett, 1970; Drillien & Wilkinson, 1964͒. It can be said, therefore, that the birth of a premature child is an event that will-in any case-increase maternal anxiety levels ͑Gorga, Stern, & Ross, 1985;Piper, Kunos, Willis, & Mazer, 1985͒. Kaplan and Mason ͑1960͒ identified some of the maternal psychological components which are associated with premature birth. Their seminal work showed how mothers of premature babies have an acute reaction to the trauma of giving birth before term.…”
Section: Discussionmentioning
confidence: 97%